Methodological reconciliation of CP and MLSS and their agreement with the maximal metabolic steady state - Ianetta, D.; Ingram, C. P.; Keir, D. A.; Murias, J. M. (Medicine & Science in Sports & Exercise, 2022)
The critical power (CP) and maximal lactate steady state (MLSS) are operational surrogates of the maximal metabolic steady state (MMSS). However, their concordance and their agreement with MMSS remain variable likely because of methodological factors.